A patient with recurrent pelvic bone metastasis after gastric cancer surgery achieved long-term survival: a case report - Wang, Yan; Hu, Xiao-Yan; Wang, Chao-Qun (Frontiers in Oncology, 2025)
IntroductionAfter gastric cancer surgery, solitary bone metastasis is very rare, and repeated pelvic metastasis has not been reported. This article reports a case of recurrent pelvic metastasis after early gastric cancer surgery, in which the patient achieved long-term survival through multiple aggressive surgeries, radiation therapy, and systemic treatment.Case PresentationThis article reports on a 67-year-old male who presented with “6 days of black stools and 2 days of fatigue.” Gastric endoscopy biopsy indicated gastric cancer, and after completing preoperative examinations, he underwent surgical treatment. The patient experienced recurrent pelvic metastases after gastric cancer surgery and underwent multiple surgeries, combined with radiotherapy and chemotherapy. In the end, he achieved long-term survival of 56 months.ConclusionsFor gastric cancer patients with isolated bone metastases, active surgery in combination with other treatment options can be taken. With the goal of reducing symptoms, improvement in quality of life and survival can be achieved.